Sistem Pendukung Keputusan Penilaian Indeks Kinerja Sales Marketing Menerapkan Metode MOORA - Arjun Nainggolan; Annisa Siregar; Mesran Mesran (Ilmu Bersama Center, 2022)
PT. ALFA SCORPII is a company that works in the sale of YAMAHA brand motorcycles. In this case PT. ALFA SCORPII requires sales marketing to be able to introduce the company's products. Problems that are often faced by PT. ALFA SCORPII is not optimal in sales marketing work in terms of introducing company products. As a result, the company may experience a decrease in revenue. One way that companies need to be able to increase sales marketing even more is that a decision support system is needed using the MOORA method. The MOORA method is a method that has a level of flexibility and ease that can be understood in separating the subjective part of an evaluation into decision criteria and decision attributes. The MOORA method can make decisions with the resulting model to solve a problem. This method is used because it can take a decision that can assess the performance of sales marketing. If the sales marketing gets the best performance assessment, then the sales marketing will get a bonus from the company. From the results calculated on the Sales Marketing Performance Index assessment, the alternative result A1 with a value of 0.4272 on behalf of Budian Arifin was obtained